HoLEP: the new 'gold standard' in bladder outflow surgery. Issue 3 (May 2017) - Banks, Freddie
Abstract : Transurethral resection of the prostate (TURP) has been the 'gold standard' procedure for benign prostatic hypertrophy (BPH) for many years. In this article the author describes Holmium Laser Enucleation of the Prostate (HoLEP) and questions why it is not more widely utilised.